APPLICATION OF THE METHOD OF THERMAL IMAGING DIAGNOSTICS IN DETERMINING THE DEGREE OF TECHNICAL CONDITION OF ELECTRICAL EQUIPMENT (Academia Science Repository, 2023)
In this article, thermal imaging diagnostics has become one of the most popular methods of maintenance and repair of electrical equipment. Its increasing popularity is due to its ability to ensure the safety of workers and identify equipment problems that can lead to system failure. In order to feel the optimal performance and productivity of the equipment, it is recommended to include Thermo-graphic checks in standard maintenance procedures. This is useful in extending the life of the equipment, which in turn reduces the need for expensive replacement. By preventing the main problems in equipment, thermal imaging has repeatedly proven to be the most reliable technique for storing and repairing electrical equipment.